Activated sludge under free ammonia treatment using gel immobilization technology for long-term partial nitrification with different initial biomass. (December 2020) - Wang, Jiawei; Yang, Hong; Zhang, Fan; Su, Yang; Wang, Shaolun
Graphical abstract: Highlights: FA treatment of activated sludge can achieve AOB enrichment. FA treatment increased the gap in growth rates between AOB and NOB. The immobilization technology promotes partial nitrification by slowing NOB growth. The initially immobilized biomass has no effect on partial nitrification. NAR reached above 86% in immobilized carrier reactor at low ammonia concentration. Abstract: To achieve stable partial nitrification, activated sludge from a wastewater treatment plant using free ammonia (FA) inhibition was immobilized in a polyvinyl alcohol carrier. After FA treatment at 16.44 mg L −1 for 1 day, due to the increased growth rate gap between ammonium-oxidizing bacteria (AOB) and nitrite-oxidizing bacteria (NOB), AOB enrichment and NOB inhibition were achieved within 12 days, with AOB and NOB accounting for 65.61 and 0.05%, respectively. Subsequently, with dissolved oxygen concentrations of 4−5 mg L −1, pH of 7.6–7.8 and temperature of 25 ± 1 °C, the immobilized carrier made of activated sludge achieved more than 90% and more than 86% of nitrite accumulation rate at the influent ammonia concentration of 90−110 mg L −1 and 35−50 mg L −1, respectively. After 50 days operation, the NOB content was 0.10%, indicating the immobilized carrier provided favorable conditions for maintaining the low NOB content. Furthermore, due to the low NOB content in the inoculum and the oxygen-limited environment formed by the increase in the AOB numbers in the carrier, immobilized carrier with different initial biomass (1, 2.5 and 5%) can achieve stable partial nitrification.